Estimating the volcanic emission rate and atmospheric lifetime of SO2 from space: a case study for Kīlauea volcano, Hawai'i - Beirle, Steffen; Hörmann, Christoph; Penning de Vries, M.; Dörner, S.; Kern, C.; Wagner, T. (Atmospheric chemistry and physics. Discussions, 2014)
Abstract. We present an analysis of SO2 column densities derived from GOME-2 satellite measurements for the Kīlauea volcano (Hawai`i) for 2007-2012. During a period of enhanced degassing activity in March-November 2008, monthly mean SO2 emission rates and effective SO2 lifetimes are determined simultaneously from the observed downwind plume evolution and meteorological wind fields, without further model input. Kīlauea is particularly suited for quantitative investigations from satellite observations owing to the absence of interfering sources, the clearly defined downwind plumes caused by steady trade winds, and generally low cloud fractions. For March-November 2008, the effective SO2 lifetime is 1-2 days, and Kīlauea SO2 emission rates are 9-21 kt day−1, which is about 3 times higher than initially reported from ground-based monitoring systems.
Im Titel ist die Ziffer 2 tiefgestellt
Gesehen am 20.11.2020
First published online: 19 August 2014